THE POLITICAL NATURE OF THE CHURCH ACCORDING TO STANLEY MARTIN HAUERWAS, WILLIAM T. CAVANAUGH AND WALTER BRUEGGEMANN - Валерій СЕКІСОВ (Cхід, 2021)
In the context of the fragmented and multiple theological discourse of postmodernism, one of the important themes that unites modern theologians and political theologians in particular is the theme of the Сhurch. However, it is not about the Сhurch in general, but about those special features and dimensions that have been forgotten or lost in the modern era. Primarily, it is related to the political dimension of the Christian community, which has become the subject of research by representatives of various theological schools. This article is devoted to the theological analysis of the ecclesiology of three prominent contemporary theologians: Stanley Hauerwas, William Cavanaugh and Walter Brueggemann. Each of them, despite belonging to different schools, different areas of interest and church affiliation, addresses the topic of the political nature of the Church in search of a constructive response to current challenges. According to Hauerwas, there should be a restoration of the vision of the Christian community as an alternative to the world in which it is located. For Hauerwas, the Church is not only a community, one of many, but a polis, which challenges both modern empires and dominant ideologies. This is exactly what William Cavanaugh is talking about, when he emphasizes that the Church's tragic loss of its own political dimension has led to the "migrations of the Holy" and the sacralization of ideologies and power structures. At the same time, Walter Brueggemann writes Church’s prophetic authority and practical capability to resist the "royal consciousness", which manifests itself in the demonstration of strength and power, as an important feature of the Church.